Preparation method and application of phosphorus-aluminum coating agent
By reacting aluminum hydroxide with phosphoric acid to form aluminum phosphate as a envelope agent for titanium dioxide, the problem of using sulfuric acid to increase costs in the prior art is solved, and the effect of improving the light resistance and weather resistance of titanium dioxide is achieved.
Patent Information
- Application Number
- CN202411923771.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-25
AI Technical Summary
In the existing titanium dioxide surface treatment methods, sodium metaaluminate is prepared using aluminum hydroxide and sodium hydroxide as the envelope agent, resulting in the need to use sulfuric acid to neutralize when adjusting the pH value, which increases the cost and salt emissions.
Aluminum hydroxide reacts with phosphoric acid to form aluminum phosphate as the envelope agent, avoiding the preparation process of sodium metaaluminate, and adjusting the pH value by diluting water, reducing the use of sulfuric acid.
It has achieved the reduction of cost and salt emissions, improved the light resistance, weather resistance and hiding power of titanium dioxide, and improved the whiteness and gloss of the product.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium dioxide preparation, and specifically relates to a preparation method and application of a phosphorus-aluminum coating agent. Background Art
[0002] The surface properties of titanium dioxide are not only related to the production method, but also closely related to its surface coating process and coating effect, which in turn affects its dispersibility, glossiness, weather resistance and oil absorption in the application system. At present, the surface treatment methods of titanium dioxide can be divided into two categories: inorganic surface treatment and organic surface treatment. Inorganic surface treatment is generally carried out by precipitation and adsorption, and one or more layers of inorganic hydrated oxide film are coated on the surface of titanium dioxide particles. The inorganic surface coating can block the lattice defects of titanium dioxide, thereby improving the weather resistance of titanium dioxide particles; the existing decorative Laminated paper mostly uses LR-952 titanium dioxide. LR-952 titanium dioxide is coated with phosphoric acid and sodium aluminate to improve the light resistance of the product in decorative laminated paper. Since the product was put on the market, its light resistance in laminated paper has been widely recognized by customers. At present, the industry generally uses aluminum hydroxide and sodium hydroxide to react to generate sodium aluminate. In order to avoid decomposition, sodium aluminate contains excessive sodium hydroxide and needs to be further neutralized with dilute sulfuric acid. After neutralization, sodium sulfate solution is produced, which will be discharged to the sewage station after three washes, causing the entire neutralization reaction to greatly increase the cost. Summary of the invention
[0003] In view of the problems in the prior art, the present invention provides a preparation method and application of a phosphate aluminum coating agent. Aluminum hydroxide is an amphoteric compound that can react with an acid to form a soluble salt. Aluminum hydroxide reacts with phosphoric acid to form a soluble salt such as aluminum phosphate, which is used as a coating agent for surface treatment of titanium dioxide. The existing method of using sodium aluminate prepared from aluminum hydroxide and sodium hydroxide as a coating agent is avoided. However, in order to adjust the pH during the coating process, sulfuric acid is used to neutralize the sodium hydroxide, which increases the cost.
[0004] The technical solution adopted by the present invention is as follows:
[0005] A method for preparing a phosphorus-aluminum coating agent, characterized in that it comprises the following steps:
[0006] Step 1: mixing phosphoric acid and aluminum hydroxide to obtain a mixture A;
[0007] Step 2: Ripening the mixture A for a certain period of time to obtain a mixture B;
[0008] Step 3: Add dilution water to mixture B to obtain a phosphate-aluminum coating agent.
[0009] Preferably, the amount of phosphoric acid added in step 1 is 6.2 m 3 , the amount of aluminum hydroxide added is 2t.
[0010] Preferably, the molar ratio of phosphoric acid added to aluminum hydroxide is 3 to 1.
[0011] Preferably, the aging time of mixture A in step 2 is 55 to 65 minutes.
[0012] Preferably, dilution water is added in step 3 until the concentration of P 2 O 5 The calculated concentration is 100-120 g / L.
[0013] Preferably, a method for coating titanium dioxide with a phosphate-aluminum coating agent, using the phosphate-aluminum coating agent according to claims 1 to 4, comprises the following steps:
[0014] Step A: injecting a quantitative titanium dioxide slurry into a coating device, stirring, measuring the concentration and adjusting it to within a qualified range to obtain slurry A;
[0015] Step B: adding a phosphorus-aluminum coating agent to slurry A, adjusting the pH, and aging to obtain slurry B;
[0016] Step C: adding a phosphate aluminum coating agent and a sodium aluminate solution to slurry B in parallel, and aging to obtain slurry C;
[0017] Step D: adding sodium aluminate solution into slurry C and aging to obtain slurry D;
[0018] Step E: adding aluminum sulfate solution and sodium aluminate solution to slurry D in parallel, and aging to obtain slurry E;
[0019] Step F: Adjust the pH value of slurry E to obtain coated titanium dioxide slurry.
[0020] Preferably, the pH value of the slurry B obtained after aging is 6.0-6.5.
[0021] Preferably, the total mass ratio of the phosphorus aluminum coating agent added in step B and step C to the titanium dioxide is P 2 O 5 The ratio of the slurry C to the slurry is 2.2 to 3:1, and the pH value of the slurry C obtained after aging is controlled to be 6.0 to 7.5.
[0022] Preferably, the pH value of the slurry D obtained after aging is 8.0-8.5.
[0023] Preferably, the total mass ratio of sodium aluminate and aluminum sulfate added in step C, D and step E to titanium dioxide is Al 2 O 3 The ratio of slurry E to slurry E was 5.0 to 6.0:1, and the pH value of the slurry E obtained after aging was 8.0 to 8.5.
[0024] Preferably, the pH value of the coated titanium dioxide slurry obtained in step F is 5.5-6.0.
[0025] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0026] 1. Aluminum hydroxide is an amphoteric compound that can react with acid to form a soluble salt. Aluminum hydroxide reacts with phosphoric acid to form aluminum phosphate, a soluble salt, which is used as a coating agent for the surface treatment of titanium dioxide, avoiding the existing use of sodium aluminate prepared from aluminum hydroxide and sodium hydroxide as a coating agent. However, in order to adjust the pH during the coating process, sulfuric acid is used to neutralize sodium hydroxide, which increases costs;
[0027] 2. This application reduces the problem of neutralizing sodium hydroxide with sulfuric acid and reduces the discharge of salt;
[0028] 3. The aluminum phosphate film layer is denser, which can improve the hydrophilicity of the pigment, increase the retention rate in the paper system, and enhance the light resistance of the laminated paper. When aluminum or aluminum compounds react with phosphoric acid, short chains between atoms such as oxygen, phosphorus, and aluminum can be formed. By increasing the pH value of the reaction system, the short chains can be quickly condensed into long chains to form a network, which has a high surface affinity and can cover other pigments, thereby increasing the absorbance of titanium dioxide. The increase in absorbance can improve the light resistance, weather resistance, and hiding power of titanium dioxide, improve the whiteness and glossiness of the product, and is not easy to change color or decompose under ultraviolet rays;
[0029] 4. In the traditional treatment process, since sodium aluminate contains excessive sodium hydroxide, it needs to be further neutralized with dilute sulfuric acid, which may cause pH rebound, that is, the pH value becomes unstable after treatment. After using the phosphate aluminum coating agent, it directly reacts with aluminum hydroxide to form aluminum phosphate. This direct reaction avoids the additional neutralization step, thereby eliminating the pH rebound phenomenon;
[0030] 5. The present application accurately controls the amount of aluminum phosphate coating agent, aluminum sulfate solution and sodium aluminate solution added in each step during the coating process, thereby maximizing the light resistance of the laminated paper after coating while saving costs. DETAILED DESCRIPTION
[0031] To make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Usually, the components of the embodiments of the present application shown can be arranged and designed in various configurations. Therefore, the following detailed description of the embodiments of the present application is not intended to limit the scope of the application claimed for protection, but merely represents the selected embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application.
[0032] Table 1 Reaction conditions and addition amount of each substance in each step of Examples 1 to 4 of the present application
[0033]
[0034]
[0035]
[0036] Comparative Example 1
[0037] The sand-grinded slurry with qualified particle size was introduced into the coating tank, and the slurry concentration was controlled to 300g / L (in terms of TiO2), and the temperature was raised to 80℃; 3.0% NaSiO 3 (SiO 2 ), homogenize for 30 min; add H 3 PO 4 Adjust pH to 3.0, adjust for 50 minutes, homogenize for 30 minutes; add 2.0% ZnCl within 60 minutes 2 and 3.0%Na 2 HPO 4 Solution, homogenize for 20 min; H 2 SO 4 Adjust pH to 5.0, adjust in 40 minutes, homogenize for 30 minutes; cool to 40℃; add Al within 40 minutes 2 (SO 4 ) 3 Adjust pH = 2.0, homogenize for 30 minutes; add sodium aluminate within 40 minutes to adjust pH = 10.0, homogenize for 30 minutes; use dilute H 2 SO 4 Adjust pH=5.5, adjust for 30 minutes, and homogenize for 120 minutes; wash with water, flash evaporate, and steam powder to obtain coated titanium dioxide.
[0038] Comparative Example 2
[0039] 55 cubic meters of alkali-soluble filtrate in the titanium dioxide production process are collected, and 50 cubic meters of upper clear filtrate are taken after sufficient sedimentation. The solid content of the clear filtrate is measured to be 8ppm, and the sodium hydroxide concentration is 15.3%; the clear filtrate is added to a mixing tank, and the sodium hydroxide concentration in the solution is adjusted to 33% by adding a measured amount of solid sodium hydroxide to obtain a mixed alkali solution; 20 cubic meters of the mixed alkali solution (equivalent to 9.0 tons of sodium hydroxide) are added to a sodium aluminate preparation tank, and steam heating is turned on; when the alkali solution is heated to 60°C, 4 tons of aluminum hydroxide powder are added at a uniform speed under continuous stirring, and the addition time is 30 minutes; continue to heat the solution until it boils, and after the aluminum hydroxide is completely dissolved, keep boiling for 15 minutes, and add a measured amount of desalted water at a uniform speed to dilute the sodium aluminate solution to an aluminum oxide content of Al2O3=95g / l, and obtain a sodium aluminate solution after sufficient cooling; weigh 60kg of deionized water, add 120g of SiO 2 The sodium silicate solution was stirred and 60 kg of uncoated rutile titanium dioxide was added to make TiO 2 The titanium dioxide slurry with a content of 800g / L is then sanded with a sand mill to make the titanium dioxide reach the original particle size; the titanium dioxide slurry that has passed the sand milling is diluted to a concentration of 300g / L with deionized water, and then classified with a hydrocyclone.
[0040]
[0041] Take the qualified overflow slurry and transfer it to the coating tank, the amount of which is TiO 2 The slurry is 50 kg in size and heated to 50°C in a coating tank by indirect steam heating. The pH value of the slurry is adjusted to 10.2, and 20 L of the sodium aluminate solution obtained in step (4) is added. Then, a 15% dilute sulfuric acid solution is added to adjust the pH value of the slurry to 6.8. Under the condition that the pH value of the slurry is maintained at 7.0 with a dilute alkali solution, 2.5 L of Al 2 O 3 Aluminum sulfate solution with a content of 100g / L is added, and the pH value of the slurry is adjusted to 6.8; the titanium dioxide slurry coated in the above steps is matured for 60 minutes under insulation and stirring, then filtered, washed with water until the filter cake resistivity reaches 252 ohms, the filter cake is dried, and then crushed with a jet mill to obtain the coated titanium dioxide powder.
[0042] Comparative Example 3
[0043] Different from Example 1, Comparative Example 3 uses dilute phosphoric acid and sodium aluminate for co-flow coating.
[0044] The coated titanium dioxide obtained in Examples 1 to 4 and Comparative Examples 1 to 3 was subjected to a QUVA aging performance test. A UVA (340) lamp was used as the light source. The sample was placed in a UV aging machine. The test conditions met the blackboard temperature of (60±2)°C and the irradiance of 0.68W / m 2 , condensation temperature (45±2)℃, test cycle period 8 hours, 4 hours of illumination / 4 hours of condensation, continuous ultraviolet accelerated light aging for 1000 hours, and the data in Table 1 below are obtained.
[0045] Table 2 Data table of light aging performance indexes of titanium dioxide obtained in Examples 1 to 4 and Comparative Examples 1 to 3 (after aging for 1000 hours in an ultraviolet accelerated aging tester)
[0046]
[0047] The above examples and comparative examples show that the aluminum-phosphorus coating agent prepared by the present invention has excellent application performance indicators as titanium dioxide for laminated paper in the laminated paper system. After 1000 hours of ultraviolet accelerated aging, its color difference △E and 60° light loss rate are better than those of the comparative example.
[0048] Table 3 Cost savings of using aluminum phosphate coating agent process coating compared with existing sodium aluminate coating
[0049]
[0050] Therefore, the present invention adopts aluminum hydroxide to react with phosphoric acid to form aluminum phosphate, a soluble salt, which is used as a coating agent for the surface treatment of titanium dioxide. The aluminum phosphate film layer is relatively dense, which can improve the hydrophilicity of the pigment, increase the retention rate in the paper system, and enhance the light resistance of the laminated paper. When aluminum or aluminum compounds react with phosphoric acid, short chains between atoms such as oxygen, phosphorus, and aluminum can be formed. By lowering the pH value of the reaction system, the short chains can be quickly agglomerated into long chains to form a network, which has a very high surface affinity and can cover other pigments, thereby increasing the absorbance of titanium dioxide. The increase in absorbance can improve the light resistance, weather resistance and hiding power of titanium dioxide, improve the whiteness and glossiness of the product, and is not easy to change color or decompose under ultraviolet rays.
[0051] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.
Claims
1. A method for preparing a phosphorus-aluminum coating agent, characterized in that: The following steps are involved: Step 1: mixing phosphoric acid and aluminum hydroxide to obtain compound A; Step 2: Ripening the mixture A for a certain period of time to obtain compound B; Step 3: Add dilution water to mixture B to obtain a phosphate-aluminum coating agent.
2. The method for preparing a phosphorus-aluminum coating agent according to claim 1, characterized in that: The amount of phosphoric acid added in step 1 is 6.2 m 3 , the amount of aluminum hydroxide added is 2t.
3. The method for preparing a phosphorus-aluminum coating agent according to claim 1, characterized in that: The aging time of mixture A in step 2 is 55 to 65 minutes.
4. The method for preparing a phosphorus-aluminum coating agent according to claim 1, characterized in that: In step 3, dilution water is added until the concentration is 100-120 g / L in terms of P2O5.
5. A method for coating titanium dioxide using a phosphorus-aluminum coating agent, characterized in that: The method of using the aluminum-phosphorus coating agent according to any one of claims 1 to 4 comprises the following steps: Step A: injecting a quantitative titanium dioxide slurry into a coating device, stirring, measuring the concentration and adjusting it to within a qualified range to obtain slurry A; Step B: adding a phosphate aluminum coating agent to slurry A, adjusting the pH, and aging to obtain slurry B; Step C: adding a phosphate aluminum coating agent and a sodium aluminate solution to slurry B in parallel, and aging to obtain slurry C; Step D: adding sodium aluminate solution into slurry C and aging to obtain slurry D; Step E: adding aluminum sulfate solution and sodium aluminate solution to slurry D in parallel, and aging to obtain slurry E; Step F: Adjust the pH value of slurry E to obtain coated titanium dioxide slurry.
6. The method for coating titanium dioxide using a phosphorus-aluminum coating agent according to claim 5, characterized in that: The pH value of the slurry B obtained after aging was 6.0 to 6.
5.
7. The method for coating titanium dioxide using a phosphorus-aluminum coating agent according to claim 5, characterized in that: The ratio of the total mass of the phosphorus aluminum coating agent added in step B and step C to titanium dioxide is 2.2-3% in terms of P2O5, and the pH value of the slurry C obtained after aging is controlled to be 6.0-7.
5.
8. The method for coating titanium dioxide using a phosphorus-aluminum coating agent according to claim 5, characterized in that: The pH value of the slurry D obtained after aging was 8.0 to 8.
5.
9. The method for coating titanium dioxide using a phosphorus-aluminum coating agent according to claim 5, characterized in that: The total mass ratio of sodium aluminate and aluminum sulfate added in step C, D and step E to titanium dioxide is 5.0-6.0% in terms of Al2O3, and the pH value of the slurry E obtained after aging is 8.0-8.
5.
10. The method for coating titanium dioxide using a phosphorus-aluminum coating agent according to claim 5, characterized in that: The pH value of the coated titanium dioxide slurry obtained in step F is 5.5-6.0.
Citation Information
Patent Citations
Phosphate film-coated powder and preparation method thereof
CN101045828A
Preparation method of high-performance titanium dioxide specially used for color masterbatch
CN110157219A
Preparation method of special high-covering-power titanium dioxide for papermaking
CN111040475A
Preparation method of high-light-resistance low-cost titanium dioxide
CN114031956A
Method for improving flowability of titanium dioxide coating slurry
CN114479519A